2019
DOI: 10.2298/abs190116029l
|View full text |Cite
|
Sign up to set email alerts
|

Liprin-β1 is upregulated in human hepatocellular carcinoma and is associated with advanced tumor stage

Abstract: Liprin-β1 is one of the broadly-expressed liprin family members. Dysregulation of liprin-β1 has been implicated in several types of human cancers. However, the expression of liprin-β1 and its clinicopathological significance in human hepatocellular carcinoma (HCC) remains elusive. We evaluated the protein expression of liprin-β1 in HCC and non-tumor liver tissues by immunohistochemistry, and investigated the relationship between liprin-β1 expression and the clinicopathological attributes of HCC. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…IHC quanti cation and statistical analysis IHC staining was evaluated in a semiquantitative method by scoring the intensity on a scale from 0 to 3 (0, negative; 1, weak or scattered staining in a minority of cells; 2, moderate or strong staining in a majority of cells; and 3, strong staining in all cells), as reported previously. [22] For the statistical analysis, the patients were strati ed into OGNLow (score of 0-1) vs OGNHigh (score of 2-3) groups. The statistical analyses were conducted using GraphPad Prism software version 6.0, and the differences between the expression of OGN and the clinic-pathological variables were examined using the Chi-Squared test and the Student's t-test.…”
Section: Immunohistochemistry (Ihc) and Quanti Cationmentioning
confidence: 99%
“…IHC quanti cation and statistical analysis IHC staining was evaluated in a semiquantitative method by scoring the intensity on a scale from 0 to 3 (0, negative; 1, weak or scattered staining in a minority of cells; 2, moderate or strong staining in a majority of cells; and 3, strong staining in all cells), as reported previously. [22] For the statistical analysis, the patients were strati ed into OGNLow (score of 0-1) vs OGNHigh (score of 2-3) groups. The statistical analyses were conducted using GraphPad Prism software version 6.0, and the differences between the expression of OGN and the clinic-pathological variables were examined using the Chi-Squared test and the Student's t-test.…”
Section: Immunohistochemistry (Ihc) and Quanti Cationmentioning
confidence: 99%
“…PPFIBP1 interacts with metastasis-associated protein S100A4, which induces invasiveness of primary tumors and promotes metastasis in melanoma [ 18 ]. Recent study also demonstrated an association between elevated PPFIBP1 expression and tumor malignancy in liver cancer [ 19 ]. However, its potential role in GBM and the mechanism by which it promotes cell migration and invasion remains incompletely understood.…”
Section: Introductionmentioning
confidence: 99%